Surface properties and stability of colloidal sludge systems in the processes of heavy metals extraction - Kalinichenko, K.V.; Nikovskaya, G.N.; Ulberg, Z.R. (Reports of the National Academy of Sciences of Ukraine, 2014)
The influences of biological and chemical extractions of heavy metals on the physical and chemical properties of sludge biocolloids and the stability of a concentrated sludge suspension formed on the municipal wastewater biological treatment plant are compared. The most significant changes occur at the biological heterotrophic process, namely: increase of the organic component by ∼10%, hydrophobization of biocolloids surface, decrease of their negative charge, and increase of the sedimentation rate by 10–20 times as compared with chemical processes.